PENGETAHUAN KELUARGA PASIEN TUBERKULOSIS SEBAGAI UPAYA PENYEMBUHAN DAN PENURUNAN ANGKA KEJADIAN TUBERKULOSIS - Eti Sumiati (LPPMK STIKES Widyagama Husada, 2021)
Tuberculosis is an infectious disease of the respiratory tract and other organs caused by the Mycobacterium tuberculosis bacteria. Tuberculosis (TB) is still one of the causes of high morbidity and mortality in the world. Indonesia is among the five countries with the highest incidence of cases. Patient adherence to medication is an important factor in the success of a treatment, and will increase the overall cure rate. The cure rate for TB patients can be influenced by several things, which one is family support, so that family knowledge of TB disease experienced by patients is very important. The aimed of this research to know the description of the patient's family knowledge about tuberculosis. This research is descriptive using data collection tools in the form of questionnaires as primary data and patient medication cards as secondary data using convenience sampling method. The subjects in the study were family members of pulmonary and extrapulmonary tuberculosis patients without complications and without MDR who were undergoing treatment for the period January-March 2019 at the Kediri Public Health Center. The results showed that as many as 11 respondents had high / good knowledge and as many as 9 respondents had low/poor knowledge.